Dimensional changes resulting from the heat treatment of EN 30B and Nimar 125 - Noble, C. F. (College of Aeronautics, 1966)
Three components have been manufactured in both EN 30B and N1MAR 125. Dimensional changes following heat treatment have been recorded and, while the sample is only small, the report serves to illustrate the potential benefits which arise from the use of a maraging steel. NIMAR 125 is shown to have reasonably predictable dimensional characteristics and thus indicates the feasibility of completing all machining operations prior to heat treatment.